Perencanaan Rancangan Bisnis Majalah Sekolah â€œMasa Kuâ€ Berbasis Mobile Application dengan Menggunakan Business Model Canvas - Saputralina, Feby Anugrah; Marlina, Elin; Sultan, Mokh Adieb (JURNAL ILMU MANAJEMEN DAN BISNIS, 2021)
Technology and entrepreneurship are spearheads in humanâ€™s life development into better, easier, and more instant. Because technology brings a lot of changes both in politic, social, economy, education, and business. Startup business growth in Indonesia itself keep raising and give positive impact to the society. Numerous startups raise in order to give every simplicity to the society, from transportation, shopping, social media, etc. almost 80% of internet users use their smartphone for social media, at least they spend 3 hours 46 minutes to surf in social media. Business Model Canvas becomes one of the options to create business design. Business Model Canvas itself is how the way business creates and gives a value to the customers. The result obtained at least more or less 38% future users have interest to this school magazine-shaped social media application, this can be said that keeping this application developed can give positive impact to both the users and the company.Â Keyword: Business Model Canvas, Startup Business, Technology and Enterpreneurship